Guiding Through the In-Between Stage: A Multiple Case Study on the Retirement Transitions of Educational Leaders - G. Zabala, Theresa; B. Dayaganon, Avee Joy (The Future of Education Journal, 2025)
This study aimed to explore the experiences, challenges and strategies of the retired educational leaders during their retirement transition stage. It employed a qualitative multiple case study approach focusing on diverse participants including classroom teacher, head teacher, school principal, education program supervisor, and schools division superintendent in Region XI, Philippines. To capture a wide range of diverse perspectives, maximum variation sampling was utilized. The primary source of data consisted of responses from the in-depth interviews (IDIs) utilizing a validated interview guide. Secondary sources such as readings from different literature sources, transcripts from triangulated interviews and field notes were also utilized to enrich and support the findings.  Data were collected through in-depth interviews and analyzed thematic analysis which generated essential themes. The data collected were analysed through thematic analysis which generated essential themes. Findings revealed five essential themes describing their common fears and uncertainties: emotional reactions to retirement, fears and uncertainties of transition, financial and practical adjustments, impact of retirement on identity and roles and strategies for a smooth retirement transition. In navigating the shift from a structured work life to a more flexible retirement lifestyle six essential themes emerged: adjusting to the loss of the routine, balancing emotional and social aspects of retirement, maintaining purpose and productivity, managing flexibility and time structure, facing challenges in transitioning to retirement and re-imagining life-post retirement.  Regarding balancing the desire for continued professional involvement and personal time during time, four essential themes surfaced: maintaining professional connections post-retirement, managing time between personal and professional activities, navigating conflicts between professional and personal time and redefining personal time. Lastly four themes described impact of financial considerations to the retirement planning of educational leaders. These were planning before retirement, financial challenges during retirement, effective financial strategies for retirement and financial stability and well-being.